When strawberries bloom - Byler, Linda (Byler, Linda. Lizzie searches for love, 2010)
Will Lizzie Glick, a high-spirited Amish teenager, give up her dream of teaching school so that her wish for a family and a marriage can come true? Based on the true experiences of the author's extended family.